2007
DOI: 10.1097/01.tp.0000268524.27506.39
|View full text |Cite
|
Sign up to set email alerts
|

BK Virus–Associated Nephropathy in Sirolimus-Treated Renal Transplant Patients: Incidence, Course, and Clinical Outcomes

Abstract: Patients treated with SRL-based immunosuppression showed an incidence at the lower end of the range described with various other contemporaneous immunosuppressive regimens and with other cohorts not undergoing BK virus polymerase chain reaction surveillance. Exposure to rATG and SPK transplantation represented risk factors for the occurrence of PVAN, which showed a pernicious course despite withdrawal of calcineurin antagonists and/or mycophenolate mofetil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 33 publications
2
51
2
Order By: Relevance
“…Since the majority of patients (7 of 9) that were treated for acute rejection received depleting antibody therapy, these data further implicate a history of depleting antibody use in BKVAN outcomes. Whether depleting antibody therapy predisposes patients to BKVAN is controversial, as some studies have found a correlation between antilymphocyte preparation use and the development of BKVAN (22,25) and others have not (9,26). It is possible that patients who are given depleting antibody therapy, either for induction or acute rejection, are at higher immunological risk and thus may be exposed to higher levels of chronic immunosuppression, which could bias the outcomes in BKVAN.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the majority of patients (7 of 9) that were treated for acute rejection received depleting antibody therapy, these data further implicate a history of depleting antibody use in BKVAN outcomes. Whether depleting antibody therapy predisposes patients to BKVAN is controversial, as some studies have found a correlation between antilymphocyte preparation use and the development of BKVAN (22,25) and others have not (9,26). It is possible that patients who are given depleting antibody therapy, either for induction or acute rejection, are at higher immunological risk and thus may be exposed to higher levels of chronic immunosuppression, which could bias the outcomes in BKVAN.…”
Section: Discussionmentioning
confidence: 97%
“…The strategy of discontinuation of CNI with maintenance SRL (2 mg/d, goal trough Ͻ8 mg/ml) and low-dose prednisone was applied to the majority of patients in the Withdrawal cohort, with considerable success in preventing graft loss while avoiding acute rejection. This strategy was first reported with success in a case series of 3 subjects (21) but with poorer outcomes when recently reported in a separate cohort of 9 patients (5 of the 9 patients lost graft function at a mean follow-up of 17.5 mo following transition to SRL/prednisone, goal SRL trough levels of 10 Ϯ 3 ng/ml) (22). Our more favorable outcomes may be due to a further reduction in immunosuppression with a lower target SRL trough compared with this series.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs in cause for these events seem to be the combination of tacrolimus, mycophenolate mofetil and monoclonal or polyclonal antibodies Nickeleit et al 1999;Nickeleit et al 2000a;Nickeleit et al 2003;Benavides et al 2007). The organ and the graft type also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…This drug acts as an anti-proliferative agent and has been suggested as an alternative treatment for viral replication control in established BKV disease. 30,31 Molecular detection of polioviruses has been considered as a gold-standard, and its effi cacy has been confi rmed by a variety of studies. 2,13,24,32 Nowadays, regarding the countless different molecular techniques available for Polyomavirus detection, 16,32 quantitative PCR with viral load defi nition is the most sensitive and specifi c approach.…”
Section: Discussionmentioning
confidence: 99%